BIOLOGICAL ACTIVE COMPONENTS OF SILENE TOMENTELLA AND THEIR PHARMACOLOGICAL PROPERTIES - Yusupova, Ugiloy Yusufovna; Ramazonov, Nurmurod Sheralievich; Bobakulov, Khairulla Mamadievich; Egamova, Feruza Rustamovna; Syrov, Vladimir Nikolaevich; Usmanov, Durbek Abdikhoshimovich (Химия растительного сырья, 2021)
In thepresent investigation isolation of chemical compounds was carried out from the aerial part of Silene tomentella, an evergreen member of the family Caryophyllaceae, using column chromatography. Identification of chemical compounds was done by various MP, TLC, IR, NMR techniques. The presence of the bioactive compound D-pinitol in this plant is being reported for the first time. Under the influence of D-pinitol, a clear tendency towards normalization of the glycogen content in the liver was also noted (it was only 10.4% lower than in intact animals). In the liver of animals, a rather sharp decrease in the content of glycogen was noted – by 63.5%, and a decrease in the activity of enzymes of the antioxidant defense of the body, characteristic of developing diabetes: SOD – by 35.1, and catalase – by 32.4%. Prophylactically – therapeutic administration of D- pinitol, which exhibits a pronounced ability to inhibit free radical oxidation processes.